Physiological Effects of Intermittent Passive Exposure to Hypobaric Hypoxia and Cold in Rats - Santocildes, Garoa; Viscor, Ginés; Pagès, Teresa; Ramos-Romero, Sara; Torres, Josep Lluís; Torrella, Joan Ramon (Frontiers in Physiology, 2021)
The benefits of intermittent hypobaric hypoxia (IHH) exposure for the health and its potential use as a training tool are well-documented. However, since hypobaric hypoxia and cold are environmental factors always strongly associated in the biosphere, additive or synergistic adaptations could have evolved in animals’ genomes. For that reason, the aim of the present study was to investigate body composition, hematological and muscle morphofunctional responses to simultaneous intermittent exposure to hypoxia and cold. Adult male rats were randomly divided into 4 groups: 1) Control, maintained in normoxia at 25°C (CTRL); 2) IHH exposed 4h/day at 4,500 m (HYPO); 3) Intermittent cold exposed 4h/day at 4°C (COLD); and 4) Simultaneously cold and hypoxia exposed (COHY). At the end of 9 and 21 days of exposure, blood was withdrawn and gastrocnemius and tibialis anterior muscles, perigonadal and brown adipose tissue, diaphragm and heart were excised. Gastrocnemius transversal sections were stained for myofibrillar ATPase and succinate dehydrogenase for fibre typing; and for endothelial ATPase to assess capillarisation. HIF 1α, VEGF and GLUT1 from gastrocnemius samples were semi-quantified by Western blotting. COLD and HYPO underwent physiological adjustments such as higher brown adipose tissue weight and increase in blood-related oxygen transport parameters, while avoiding some negative effects of the chronic exposure to cold and hypoxia, such as body weight and muscle mass loss. COHY presented an additive erythropoietic response and was prevented from right ventricle hypertrophy. Intermittent cold exposure induced muscle angiogenesis and IHH seems to indicate better muscle oxygenation through fibre area reduction.